THE METHOD OF ECG DISPERSION MAPPING IN ASSESSMENT OF ELECTRICAL ACTIVENESS OF ATRIA AND VENTRICLES - G. G. Ivanov; S. P. Leshchinsky; N. A. Bulanova (Сеченовский вестник, 2022)
The ECG dispersion mapping method is a relatively new method for diagnosing the state of myocardium. It is based on a computer rendering of the electrical microalternations of ECG signal assigned to specific parts of the heart (two atria, two ventricles). Dispersive mapping method can be used in all areas of medicine that require early diagnosis and detection of changes and disorders of electrophysiological properties of myocardium. This paper describes the technical aspects of this method, as well as its use.